Портрети Михайла Драгоманова - Третяченко, Т. (Слово і Час, 2011)
У статті йдеться про історію відомих фотопортретів М. Драгоманова, уточнюється датування
фотоматеріалів у виданнях творів Драгоманова та в літературі про нього. The paper deals with the history of well-known photographic portraits of Mykhaylo Drahomanov,
and specifies the dating of photographic pictures used in different editions of his works as well as in
critical reviews of his oeuvre. В статье подана история известных фотопортретов
М. Драгоманова, уточняется датировка фотоматериалов в
изданиях произведений Драгоманова и в литературе о нем.